2017
DOI: 10.22276/ethnoscientia.v2i1.84
|View full text |Cite
|
Sign up to set email alerts
|

Preferências, Tabus Alimentares E Uso Medicinal De Peixes Na Reserva De Desenvolvimento Sustentável Barra Do Una, São Paulo

Abstract: RESUMOO relacionamento íntimo entre homem e natureza nas comunidades costeiras (caiçara) em São Paulo pode revelar informações importantes sobre o meio ambiente. Os peixes constituem um dos recursos naturais mais importantes para as comunidades costeiras tradicionais no Brasil, com relevância ambiental, cultural e econômica. A presente pesquisa teve como objetivo analisar as preferências, os tabus alimentares e as indicações medicinais de espécies de peixes na Reserva de Desenvolvimento Sustentável da Barra do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…In our study, the use of medicinal plants was reported, but termite smoke was the most prevalent remedy, and this form of treatment has been reported as widely employed in Rio Negro (Amazonas) 12 . Immersion in hot water was used by some interviewees to treat their injuries, and it has been shown to provide pain relief 14 . The use of mandi eyes as a remedy was also reported by injured fishermen in our study, similar to a report by Prado (2017) 14 in a study undertaken at the Barra do Una Reserve (São Paulo).…”
Section: /6mentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the use of medicinal plants was reported, but termite smoke was the most prevalent remedy, and this form of treatment has been reported as widely employed in Rio Negro (Amazonas) 12 . Immersion in hot water was used by some interviewees to treat their injuries, and it has been shown to provide pain relief 14 . The use of mandi eyes as a remedy was also reported by injured fishermen in our study, similar to a report by Prado (2017) 14 in a study undertaken at the Barra do Una Reserve (São Paulo).…”
Section: /6mentioning
confidence: 99%
“…Immersion in hot water was used by some interviewees to treat their injuries, and it has been shown to provide pain relief 14 . The use of mandi eyes as a remedy was also reported by injured fishermen in our study, similar to a report by Prado (2017) 14 in a study undertaken at the Barra do Una Reserve (São Paulo). In that study, respondents reported having placed the eyes of the mandi fish over the wounded region to relieve the pain caused by the mandi's spine.…”
Section: /6mentioning
confidence: 99%
“…Tanto a disponibilidade da fauna local em abundância e riqueza, quanto o acesso a outras proteínas são apontadas como explicação para ausência ou presença de tabus. Quando os recursos alimentares são escassos as restrições tendem a relaxar, ou seja, as dietas ficam mais diversificadas e a presença de tabus não ocorrem com frequência (BEGOSSI et al, 2004;PRADO et al, 2017).…”
Section: Tabus Alimentares Associados à Fauna Cinegéticaunclassified
“…Sua praia tem aproximadamente 2 km de extensão e na comunidade existe um posto de saúde, uma escola (que atende alunos do ensino fundamental), um Centro Comunitário, uma igreja Assembleia de Deus e uma capela de Santo Antônio. Este núcleo de famílias localiza-se a aproximadamente 28 km do centro de Peruíbe (Prado et al, 2017, Prado e Ramires, 2020.…”
Section: Metodologiaunclassified